STUDI KUALITAS TANAH PADA TOPOSEQUEN SUB DAS POBOYA, KOTA PALU - Widiastuti, Wiwi; Rajamudin, Ulfiyah A.; Isrun, Isrun (AGROTEKBIS, 2016)
The purpose of this research is to study and evaluate the soil quality level criteria on toposekuen subzone Poboya based on several different topography. The method used is descriptive method variables explorative approach conducted through field surveys and supported by the results of soil analysis in the laboratory. Then proceed to describe the results of studies assessing soil quality scoring method on each indicator. The results showed that the soil in the area Sub Das Poboya quality criteria are less healthy soil and healthy. Soil quality with less healthy criteria how the peaks and concave regions which have the highest scoring value of 2.72 (on a sunken area) and the value of the lowest scoring is 2, 36 (the peak area). While healthy soil quality criteria are in the valley and convex areas which have the highest scoring value of 3.27 (in the valley) and the value of the lowest scoring is 3.09 (on a convex area).Â Key Words : Soil quality, Toposekuen.